2009
DOI: 10.1016/j.molonc.2009.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Up‐regulated Proteins in the Fluid Bathing the Tumour Cell Microenvironment as Potential Serological Markers for Early Detection of Cancer of the Breast

Abstract: Breast cancer is by far the most common diagnosed form of cancer and the leading cause of cancer death in women today. Clinically useful biomarkers for early detection of breast cancer could lead to a significant reduction in mortality. Here we describe a detailed analysis using gel-based proteomics in combination with mass spectrometry and immunohistochemistry (IHC) of the tumour interstitial fluids (TIF) and normal interstitial fluids (NIF) collected from 69 prospective breast cancer patients. The goal of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
84
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 94 publications
(86 citation statements)
references
References 116 publications
1
84
0
1
Order By: Relevance
“…The mean age of the patients was 45.6 years with a minimum of 40 years and a maximum of 53 years. Clean fresh leiomyoma and myometrium (500 µg each) were washed with sterile PBS at 4˚C as previously described (16). Tissues were cut into sections of ~1-3 mm 3 , rinsed in sterile PBS at 4˚C and placed in sterile Petri dishes with 5 ml sterile PBS.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mean age of the patients was 45.6 years with a minimum of 40 years and a maximum of 53 years. Clean fresh leiomyoma and myometrium (500 µg each) were washed with sterile PBS at 4˚C as previously described (16). Tissues were cut into sections of ~1-3 mm 3 , rinsed in sterile PBS at 4˚C and placed in sterile Petri dishes with 5 ml sterile PBS.…”
Section: Methodsmentioning
confidence: 99%
“…The tumor interstitial fluid (TIF) consists of a liquid phase that accumulates inside the tumor interstitium (15). In addition to the group of blood soluble proteins, it contains a large subset of abnormal proteins released by tumor cells through classical secretion, non-classical secretion, membrane protein shedding and secretion via exosomes (16). The proteomic approach has been described for leiomyoma tissue (17) and plasma (18).…”
Section: Introductionmentioning
confidence: 99%
“…The IF was obtained as previously described (14,15). Two samples (300 mg each) were collected from each patient: One from the unaffected myometrium and one from the central area of the leiomyoma.…”
Section: Preparation Of Ifmentioning
confidence: 99%
“…Schulz et al [23] compared the protein expression pattern of triple-negative breast carcinomas versus those being positive for HER2 and negative for the hormone receptors (HER2+, ER-, PR-) by 2-D DIGE and mass spectrometry. They obtained differential expression patterns for several glycolytic enzymes (MDH2, PGK1, TKT, Aldolase1), cytokeratins (CK7, 8,9,14,17,19), further structure proteins (vimentin, fibronectin, L-plastin), for NME1-NME2, lactoferrin, and members of the Annexin family. They suggest that the identified marker proteins may advance a more detailed characterization of triple-negative breast cancers and may contribute to the development of better treatment strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Over expression of Cyclin E1 [5], metastasis-related proteins [6] as well as glycolytic enzymes, cytokeratins, and structural proteins [7] were seen in triple negative breast cancers. Gromov et al [8] identified 46 proteins that were upregulated in triple negative tumors. Zhang et al [9] have studied proteomic signature in 3 breast cancer cell lines of inflammatory breast cancer (SKBR3, SUM149 and SUM190).…”
mentioning
confidence: 99%